Teachers’ Strategies In Teaching Speaking At The Eleventh Grade Of MAN 1 Kebumen - Hastri Firharmawan; Kurnia Khikmayanti Elfira (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Teachers' strategies plays important roles in teaching. However, one applicable strategy in a certain context might not be applicable for another teaching context. This research was conducted at MAN 1 KEBUMEN for one month. The subjects of this study were English teachers and eleventh grade students. The purpose of this study was to explore the strategies used by the teachers in teaching speaking at the eleventh grade. This study also provided questionnaires to students to determine students' responses to the strategies used by the teachers in teaching speaking. The research method used descriptive qualitative to describe the strategies used by teachers in teaching speaking. In addition, the research also described student responses to the strategies used by the teachers. The data was collected by using interviews, questionnaires, and documentation. The results of the study found: First, there were six strategies used by the teachers in teaching speaking, namely role playing, dialogues, discussion, picture description, playing cards, and brainstorming. Second, it was found that the students were happy with the strategies used by the teachers.